People, profits, and politics in the Eastern Cape chokka squid fishery: the socio-economics of an unstable resource - Paterson, Frances Tessa (School of Economics, 2022)
This study examines socio-economic issues confronting the chokka squid fishery in South Africa's Eastern Cape, particularly in the towns of St Francis Bay, Humansdorp and Jeffreys Bay. It examines the implications of two key issues challenging the industry: the volatility of chokka squid catches, and the government's recent proposal that, to further transformation, 25% of the sector's commercial rights should be reallocated to small-scale fishing cooperatives. It is argued that the socio-economic effects of catch volatility flow from the institutional structure of the fishery and the labour contracts in it, specifically the link between fishers' earnings and their catches. These are further linked to the local economy to which the fishery and its workers are closely tied. This thesis examines the ability of small-scale fishing co-operatives to participate efficiently in the sector and the potential impact of the proposed rights reallocation on the economic viability of existing firms. The primary data used was collected through personal communications with key sector participants. Possible solutions to the two issues examined are proposed. Alternative approaches to transformation and empowerment within the chokka sector are suggested.